2022
DOI: 10.1186/s12886-022-02717-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcorneal but not transpalpebral electrical stimulation disrupts mucin homeostasis of the ocular surface

Abstract: Purpose Transcorneal electrical stimulation (TcES) is increasingly applied as a therapy for preserving and improving vision in retinal neurodegenerative and ischemic disorders. However, a common complaint about TcES is its induction of eye pain and dryness in the clinic, while the mechanisms remain unknown. Method TcES or transpalpebral ES (TpES) was conducted in C57BL6j mice for 14 days. The contralateral eyes were used as non-stimulated controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…ES is currently being explored across various research areas to understand its beneficial effects 11–14 . It has proven its efficacy in regenerative medicine research and studies have also shown that it has the potential to regulate epigenetic events 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ES is currently being explored across various research areas to understand its beneficial effects 11–14 . It has proven its efficacy in regenerative medicine research and studies have also shown that it has the potential to regulate epigenetic events 15 .…”
Section: Introductionmentioning
confidence: 99%
“…ES is currently being explored across various research areas to understand its beneficial effects. [11][12][13][14] It has proven its efficacy in regenerative medicine research and studies have also shown that it has the potential to regulate epigenetic events. 15 In a recent study, nanosecond pulsed electric fields was shown to cause downregulation of DNA methylation transferase 1 (DNMT1), which mediated the DNMT1-OCT4/ NANOG axis resulting in the differentiation potential of mesenchymal stem cells.…”
mentioning
confidence: 99%